Platelet Inflammatory Response to Stress - Cognasse, Fabrice; Laradi, Sandrine; Berthelot, Philippe; Bourlet, Thomas; Marotte, Hubert; Mismetti, Patrick; Garraud, Olivier; Hamzeh-Cognasse, Hind (Frontiers in Immunology, 2019)
Blood platelets play a central hemostatic function, they repair damaged vascular epithelium, and they also play immune defense roles having the capacity to produce and secrete various cytokines, chemokines, and related products. Platelets therefore mediate inflammation, express and use receptors to bind, amongst others, infectious pathogen moieties and endogen ligands. Platelets contribute to effective pathogen clearance. According to the danger theory of Matzinger, the immune system does not simply distinguish whether an entity is foreign or not, it mainly determines whether it will cause damage to the body. Damage‐associated molecular patterns (DAMP) are danger signals released during inflammatory stress such as burns, trauma and infection. Each pathogen is recognized by its specific molecular signature or pathogen‐associated molecular pattern (PAMP). Recent data demonstrate that platelets have the capacity to sense external danger signals (DAMPs or PAMPs) differentially through a distinct type of pathogen recognition receptor (such as the Toll-like receptors) and that they regulate the innate immune response for pathogens and/or endogenous molecules presenting several types of “danger” signals using a complete signalosome. Platelets therefore use complex tools for mediating a whole range of functions from danger sensing to tissue repair. Moreover, we noted that the secretory capacity of stored platelets over time or of platelets undergoing stress lesions upon collection, processing, and storage are considered as stress signals. Blood platelets are involved in inflammation and various steps of innate immunity through the release of a plethora of immunomodulatory cytokines, chemokines and associated molecules, i.e. biological response modifiers (BRMs). The main focus of this review is the "Platelet Inflammatory Response to Stress" function of platelets in an infectious or non-infectious context.